2018
DOI: 10.1007/s00256-018-3039-9
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dose reduction for musculoskeletal computed tomography of the pelvis with preserved image quality

Abstract: Subjective and objective image quality for pelvic CT examination remains adequate, despite a substantially reduced radiation dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Applying a single limit is not practical and reported radiation exposures vary widely. For example, reported mean exposure dose for pelvis ldCT [1] was three times another recent report [2] and 47 times the dose of a dedicated SIJ protocol [3 ▪▪ ]. This latter study confirmed that by using tin filtration, SIJ ldCT radiation dose can be reduced even further to 0.11 mSv, which is the same dose as PA and lateral chest radiography, while maintaining diagnostic quality.…”
Section: What Is Low-dose Computed Tomography Of the Axial Skeleton?supporting
confidence: 66%
See 1 more Smart Citation
“…Applying a single limit is not practical and reported radiation exposures vary widely. For example, reported mean exposure dose for pelvis ldCT [1] was three times another recent report [2] and 47 times the dose of a dedicated SIJ protocol [3 ▪▪ ]. This latter study confirmed that by using tin filtration, SIJ ldCT radiation dose can be reduced even further to 0.11 mSv, which is the same dose as PA and lateral chest radiography, while maintaining diagnostic quality.…”
Section: What Is Low-dose Computed Tomography Of the Axial Skeleton?supporting
confidence: 66%
“…Applying a single limit is not practical and reported radiation exposures vary widely. For example, reported mean exposure dose for pelvis ldCT [1] was three times another recent report [2] and 47 times the dose of a dedicated SIJ protocol [3 radiography, while maintaining diagnostic quality. There is also no agreement on whether any chosen limit would apply to each location separately or to the entire body.…”
Section: What Is Low-dose Computed Tomography Of the Axial Skeleton?mentioning
confidence: 90%